Industry 4.0: limitation or benefit for success? - Milošević, Isidora Miloje; Arsić, Sanela; Glogovac, Maja; Rakić, Ana; Ruso, Jelena (Serbian Journal of Management, 2022)
The fourth industrial revolution is a significant driving force framing companies' digital, social, and economic needs. This concept considerably influences the outcomes of businesses by increasing cost-effectiveness, quality, and effectiveness. However, studies on performance outcomes of Industry 4.0 in Serbia are still scarce. The available literature mainly deals with papers that observe Industry 4.0 from only one point of view, most often positive or negative effects on business success. A literature gap was observed that would fulfil the observed Industry 4.0 from two opposite aspects, positive or negative. To overcome the literature gap, this paper aims to observe if Industry 4.0 is perceived as facilitating or limiting for business success. The study provides a more objective approach to observing and decision-making in Industry 4.0 acceptance. To support this contribution, the paper provide a deeper analysis of the factors that impact the financial, operational, and strategic performance outcomes associated with Industry 4.0. Considered factors are attitude toward digitalization, limitations of digitalization, and expected benefits of digitalization. The results gathered through 134 valid questionnaires are evaluated using Structural Equation Model. These results show that all relationships and impacts are confirmed except the influence of internal limitations on performance outcomes. These findings are encouraging for companies wanting to transfer to Industry 4.0.
Keywords: Industry 4.0; digitalization; attitude; limitations; benefits; performance outcomes